Radio Komersil Dakta 107 FM Bertahan melalui Strategi Dakwah - Nur Baeti; Armawati Arbi (INTERAKSI PERADABAN: Jurnal Komunikasi dan Penyiaran Islam, 2021)
Interaction between pendakwah and listeners in on air program in stage 5  Media internal dan media external stage 6 negociated  to make modification and change  format radio to strive for life through strategic dakwah in off air program although identity of radio Dakta was not dakwah radio.This articlewill answer strategy 1)how  Dakta radio framed symbolic reality  on air? And how  Dakta radio modified or change its identity to state objective reality in Bekasi City in post-production? The  mass media social construction on social reality Burhan Bungin theory. The research  uses qualitative approach with constructivism paradigm. Asmuni Syukir, five principles can streght strategic dakwah It found 1.in frame simbolic reality on air program in stages 5: a)various pendakwah from different ideology/mahzab for uniting Muslim listeners,b) competency of pendakwah by using back to alQuran and Hadits,not Mahzab, c) motivating of listeners 25-50 years old, d) leading and teasing listeners in on air program and off air program in state objective reality  a) by using new media,radio streaming,and various events in off air program.and b) its identity have Islamic nuance, c) it has changes five times of format;